Educational Construction in Ibn Khaldun's Philosophy: Literary Analysis and Contribution to Contemporary Islamic Education - Hamirudin; Saddam Husein (IAIN Ambon, 2024)
This article aims to analyze the construction of education in Ibn Khaldun's philosophy and explore its contribution to contemporary Islamic education through a literature-based approach. Using library research methods, this study examines Ibn Khaldun's major work, Muqaddimah, along with various secondary literatures that discuss his philosophical views on education. The findings reveal that Ibn Khaldun views education as a gradual social process, emphasizing practical and moral learning, and the importance of critical, non-dogmatic education. This concept is relevant to the challenges of modern Islamic education, particularly in efforts to integrate intellectual and ethical education to build a generation that contributes to the advancement of civilization.